2006
DOI: 10.1111/j.1365-3156.2006.01564.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting uptake of voluntary counselling and testing in a real‐life setting in a mother‐and‐child center in Ouagadougou, Burkina Faso

Abstract: Summaryobjective To identify factors predicting uptake of voluntary HIV counselling and testing in pregnant women.methods All pregnant women receiving ante-natal group health education at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 16 publications
2
40
1
3
Order By: Relevance
“…Similarly, in a study conducted in Burkina Faso, the uptake rate of VCT increased linearly with age, being particularly low among adolescents (15-19 years) [67] . Enosolease and Offor [85] have shown that older Nigerian women had higher rates of acceptance of HIV testing.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, in a study conducted in Burkina Faso, the uptake rate of VCT increased linearly with age, being particularly low among adolescents (15-19 years) [67] . Enosolease and Offor [85] have shown that older Nigerian women had higher rates of acceptance of HIV testing.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…Enosolease and Offor [85] have shown that older Nigerian women had higher rates of acceptance of HIV testing. It has been suggested that older women may be more aware of a higher cumulative risk of infection and are more likely to take autonomous decisions [67] . Other studies have found that older age was actually associated with test refusal [58,66] .…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our experience, PMTCT (Prevention of Mother-to-Child Transmission) activities were crucial to identify HIV infected pregnant women. Even if VCT (Voluntary Counseling and Testing) uptake rate was far than optimal using an opt-in strategy [4], women were nonetheless favored since their access to care resulted to be earlier than that of their male partners. Females might also be more prone to screening wherever gender context permits [5];…”
mentioning
confidence: 99%